Follow-up CT and CT angiography after intracranial aneurysm clipping and coiling-improved image quality by iterative metal artifact reduction. - Bier, Georg; Bongers, Malte; Hempel, Johann-Martin; Örgel, Anja; Hauser, Till-Karsten; Ernemann, Ulrike; Hennersdorf, Florian (Neuroradiology, 2017)
Purpose: This paper aims to evaluate a new iterative metal artifact reduction algorithm for post-interventional evaluation of brain tissue and intracranial arteries. Methods: The data of 20 patients that underwent follow-up cranial CT and cranial CT angiography after clipping or coiling of an intracranial aneurysm was retrospectively analyzed. After the images were processed using a novel iterative metal artifact reduction algorithm, images with and without metal artifact reduction were qualitatively evaluated by two readers, using a five-point Likert scale. Moreover, artifact strength was quantitatively assessed in terms of CT attenuation and standard deviation alterations. Results: The qualitative analysis yielded a significant increase in image quality ( p = 0.0057) in iteratively processed images with substantial inter-observer agreement ( ĸ = 0.72), while the CTA image quality did not differ ( p = 0.864) and even showed vessel contrast reduction in six cases (30%). The mean relative attenuation difference was 27% without metal artifact reduction vs. 11% for iterative metal artifact reduction images ( p = 0.0003). Conclusions: The new iterative metal artifact reduction algorithm enhances non-enhanced CT image quality after clipping or coiling, but in CT-angiography images, the contrast of adjacent vessels can be compromised.